Musculoskeletal problems among workers in a garment industry, at Tirupur, Tamil Nadu - Ravichandran, Sreesupria Purushothaman; Shah, Pankaj Badamilal; Lakshminarayanan, Kannan; Ravichandran, Abinayaa Purushothaman (Indian Journal of Community Health, 2016)
Background: Every occupation has its own ill effects on health. Garment workers are denied of their basic rights and less importance is given to their health. Their health status also depends on their access to treatment and availability of healthcare facilities. Aims & Objectives: To estimate the prevalence, health seeking pattern and associated factors for musculoskeletal problems among garment workers and to assess the level of exposure of individual workers to upper limb musculoskeletal loads. Materials and methods: A cross sectional study was conducted among 380 workers in a garment industry, at Tirupur over a period of two months. Interview was conducted using a structured pretested questionnaire including Nordic Musculoskeletal Questionnaire and Numerical Pain Rating Scale. Level of exposure to musculoskeletal load was assessed using RULA tool. Statistical analysis was done using SPSS 19 version. Results: 77.6% of the workers had musculoskeletal problems. The most common sites affected were neck (32.1%), knee (28.7%) and low back (26.6%). More than half of the workers experienced moderate pain in all body parts. 54.2% sought health care and 40% among them preferred government hospital. Only 8.7% workers had acceptable posture. Conclusion: Health problems among garment workers are one of the areas of public health concern in our country. Reducing the work strain and providing a supportive workplace environment will have a favorable impact on work productivity